1999
DOI: 10.1046/j.1365-2982.1999.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Isopower maps of the electrogastrogram (EGG) after total gastrectomy or total colectomy

Abstract: Isopower or topographic electrogastrograms (EGG) correspond to topographic electroencephalograms. Both project the topographic localizations of the spectral frequencies on the abdominal surface or scalp. This paper compares the pre-operative control isopower EGG maps with those of total gastrectomy or total colectomy. EGGs were recorded simultaneously at 27 locations on the epigastro-abdominal surface. Spectral analysis by the maximal entropy method (MEM) was performed and the ensemble means of pre-prandial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(83 citation statements)
references
References 10 publications
4
78
1
Order By: Relevance
“…Anxiety has also been reported to facilitate antral meal retention (Lorena et al, 2004). The epigastric 3-and 6-cpm groups electrical activity in the EGG were suggested to reflect those of the colon on the basis of the EGG results obtained after total gastrectomy (Pezzola et al, 1989;Homma et al, 1995Homma et al, , 1999. We have reported that gastric, intestinal and colonic myoelectric activity can be recorded using EGG (Homma et al, 1995: Homma, 1997: Homma et al, 1999, 2000.…”
Section: Gastric Activitymentioning
confidence: 93%
See 4 more Smart Citations
“…Anxiety has also been reported to facilitate antral meal retention (Lorena et al, 2004). The epigastric 3-and 6-cpm groups electrical activity in the EGG were suggested to reflect those of the colon on the basis of the EGG results obtained after total gastrectomy (Pezzola et al, 1989;Homma et al, 1995Homma et al, , 1999. We have reported that gastric, intestinal and colonic myoelectric activity can be recorded using EGG (Homma et al, 1995: Homma, 1997: Homma et al, 1999, 2000.…”
Section: Gastric Activitymentioning
confidence: 93%
“…The methods used for recording and analyzing EGGs were the same as in the previous studies (Homma et al, 1999: Homma, 2005. Briefly, unipolar EGGs were recorded from the 16 locations (channels, ch) from the thoraco-abdominal skin surface (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations